2015
DOI: 10.1155/2015/536762
|View full text |Cite
|
Sign up to set email alerts
|

Dust Aerosols Detected Using a Ground-Based Polarization Lidar and CALIPSO over Wuhan (30.5°N, 114.4°E), China

Abstract: The vertical distribution, horizontal range, and optical properties of Asian dust were obtained using a ground-based depolarization lidar and Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) over a two-year measurement period (2010–2012) in Wuhan (30.5°N, 114.4°E), China. The depolarization lidar registered 13 dust events, most of which occurred in the spring (5 events) and winter (6 events). The dust layers occurred at heights of approximately 1.4–3.5 km. The horizontal ranges of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…reason why the color ratio of transported anthropogenic dust is greater than that of pure dust is that the dust is mixed with smoke or anthropogenic aerosols during its transport, causing slight growth of the mixed aerosol. In the source regions, the color ratios of dust particles are between 0.7-1.0 (Huang et al, 2007;He et al, 2015). Huang et al (2007) found the mean color ratio of the frequently observed dust aerosols at heights of 4-7 km over the Tibet Plateau in the summer to be 0.83.…”
Section: Comparison Of the Optical Properties Of Two Types Of Dustmentioning
confidence: 99%
“…reason why the color ratio of transported anthropogenic dust is greater than that of pure dust is that the dust is mixed with smoke or anthropogenic aerosols during its transport, causing slight growth of the mixed aerosol. In the source regions, the color ratios of dust particles are between 0.7-1.0 (Huang et al, 2007;He et al, 2015). Huang et al (2007) found the mean color ratio of the frequently observed dust aerosols at heights of 4-7 km over the Tibet Plateau in the summer to be 0.83.…”
Section: Comparison Of the Optical Properties Of Two Types Of Dustmentioning
confidence: 99%
“…7e-h). The low dust depolarization ratio values observed over the densely populated and highly industrialized regions suggest the occurrence of a mixture of non-spherical aerosols with particles of anthropogenic origin (Heese and Wiegner, 2008). Conversely to the aerosol layers close to the urban or industrial regions, the elevated layers over China and India are characterized by intermedi-E. Proestakis et al: Nine-year spatial and temporal evolution of desert dust aerosols ate dust depolarization ratio values, from about 15 to 25 %.…”
Section: Conditional Dust Extinction Coefficientmentioning
confidence: 99%
“…The reason why we could use VDR to discriminate pure dust and polluted dust aerosol is that dust mixes with smoke or other anthropogenic aerosols during transport, which makes the mixed aerosol nearly spherical. For example, dust particles can be fully mixed with inorganic salt (Fan et al, ; Shen et al, ; Sun et al, ); pollution elements such as Se, Ni, Pb, Br, Cu (Zhang et al, ); black carbon (Kim et al, ); VOCs; (volatile organic compounds) and polyaromatic hydrocarbon during long‐range transport (He & Yi, ).…”
Section: Comparison Of the Optical Properties Of Two Types Of Dustmentioning
confidence: 99%
“…When the CR was larger than 0.8, it was mostly pure dust. In the source regions, the CR values of dust particles were between 0.7 and 1.0 (He & Yi, 2015;.…”
Section: 1029/2018jd028957mentioning
confidence: 99%